Sosialisasi Peluang Dunia Kerja dan Kewirausahaan di Bidang Olahraga : Sosialisasi Peluang Dunia Kerja dan Kewirausahaan di Bidang Olahraga - Fera Ratna Dewi Siagian; Maria Andriani Barek Ladjar; Jurdan Martin Siahaan (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
The problem found was that there were still alumni of the Physical Education and Health Study Program, FKIP Undana, who were unemployed, and the majority were competing to take the CPNS test as their main choice in finding work. Therefore, the community service team provided a solution by conducting a Socialization of Job Opportunities, Further Studies and Entrepreneurship in the Sports Sector. The objectives of this activity were 1) to provide information about professional career opportunities in the sports sector, 2) to foster enthusiasm and motivation among the community, students and alumni of the Physical Education and Health Study Program to start a business in the sports sector, and 3) to provide a direct discussion forum with sports entrepreneur speakers. The targets of this activity were Alumni and students of the Physical Education and Health Study Program, FKIP Undana, who had completed their graduation but had not yet graduated and who had graduated but had not yet found employment. The resource person in this socialization activity was Jimi W. B. Sianto, S.E., M.M, he is an expert in the field of Sport Edupreneurship as well as the Founder of D&B Enterprise Event Organizer in 2001, KONI NTT Management, and Chairman of AFP NTT who is very suitable to provide enlightenment for the socialization participants in particular and in general for all groups who are looking for work and are currently engaged in the world of entrepreneurship, especially in the field of sports. The results of this activity there were many discussions between the resource person and alumni and students which showed their interest in engaging in the business world in the business sector. This shows that this community service activity is important to overcome problems for alumni who have not found work.